Enhanced Two-Step Nearest Level Control with Enhanced Power Quality for Electric Ship System - Hui Hwang Goh; Jiaru Sun; Xue Liang; Dongdong Zhang; Wei Dai; Shaojian Song; Tonni Agustiono Kurniawan; Kai Chen Goh (CSEE Journal of Power and Energy Systems)
The implementation of modular multilevel converters (MMC) in an electric ship to create a medium voltage direct current (MVDC) energy conversion system that is efficient, small, dependable, and easily scalable has garnered considerable interest. In this research, an improved two-step nearest level control (E-NLC) is presented for MMC with a three-level submodule (3L-SM) as the rectifier of the electric ship power generation units in order to ease the economical and reliable operation of MMCs in MVDC systems. To achieve DC fault-clearing capability, the use of MMC with 3L-SM minimizes the number of switching devices when compared to the regular MMC topology. The suggested E-NLC scheme aims to reduce total harmonic distortion (THD) and achieve the nearest zero common mode voltage (CMV). The output voltage vector of the three phases is tuned using eight candidate vectors capable of suppressing CMV rather than the nearest-level vector, and the rounding function is modified to improve harmonic performance by increasing the approximation between stepped and modulated waves. The generator-connected MMC with THD reduction and CMV elimination maximizes the mover's protection in the generating unit of the electric ship's MVDC system. Simulation and experiment results validate the efficacy of the suggested approach with respect to steady-state and dynamic-state performance.